Criminal Case Handling in Indonesia: Challenges, Reforms, and Future Directions - Muhammad Jordan Figo Azhari (Proceeding International Conference Restructuring and Transforming Law, 2024)
This article delves into the intricacies of criminal case handling in Indonesia, shedding light on the challenges it faces, recent reforms, and future prospects. The introduction provides an overview of the existing issues in the Indonesian criminal justice system. It discusses the significant backlog of cases, the overburdened judiciary, and the need for systemic improvements. The methods section outlines the research approach, incorporating data analysis, interviews with legal experts, and a review of relevant literature. What sets this article apart from previous research is its comprehensive examination of the multifaceted nature of criminal case handling in Indonesia, addressing not only the legal aspects but also the social and institutional dimensions. The results and discussion section presents key findings, including insights into the impact of recent reforms, challenges faced by law enforcement agencies, and the role of corruption in case processing. In conclusion, this article underscores the importance of ongoing reforms and offers recommendations to enhance the efficiency and fairness of the criminal justice system in Indonesia. It emphasizes the need for a holistic approach that addresses systemic issues and promotes transparency, accountability, and judicial independence.